2002
DOI: 10.1073/pnas.202474099
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and acidosis activate cardiac myocyte death through the Bcl-2 family protein BNIP3

Abstract: Coronary artery disease leads to injury and loss of myocardial tissue by deprivation of blood flow (ischemia) and is a major underlying cause of heart failure. Prolonged ischemia causes necrosis and apoptosis of cardiac myocytes and vascular cells; however, the mechanisms of ischemia-mediated cell death are poorly understood. Ischemia is associated with both hypoxia and acidosis due to increased glycolysis and lactic acid production. We recently reported that hypoxia does not induce cardiac myocyte apoptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
423
3
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(455 citation statements)
references
References 37 publications
27
423
3
2
Order By: Relevance
“…The germ-line BNIP3 knockout mouse showed no detectable developmental or functional abnormalities in any organ system, including the hematopoietic system wherein increased numbers of lymphoid, myeloid and erythroid cells have been described for other BH3-only factor gene knockout models (Bouillet et al, 1999;Ranger et al, 2003;Diwan et al, 2007a). This is consistent with the concept that BNIP3 functions almost exclusively in an inducible manner, and that ischemia is critical to increase its expression and possibly to activate it post-translationally (Kubasiak et al, 2002;Kubli et al, 2008). Accordingly, systemic anti-BNIP3 therapy has the potential to prevent post-ischemic cardiac remodeling without untoward consequences in other tissues.…”
Section: Transgenic Cardiac Overexpression Studies Of Bnip3 and Nix/bsupporting
confidence: 81%
See 2 more Smart Citations
“…The germ-line BNIP3 knockout mouse showed no detectable developmental or functional abnormalities in any organ system, including the hematopoietic system wherein increased numbers of lymphoid, myeloid and erythroid cells have been described for other BH3-only factor gene knockout models (Bouillet et al, 1999;Ranger et al, 2003;Diwan et al, 2007a). This is consistent with the concept that BNIP3 functions almost exclusively in an inducible manner, and that ischemia is critical to increase its expression and possibly to activate it post-translationally (Kubasiak et al, 2002;Kubli et al, 2008). Accordingly, systemic anti-BNIP3 therapy has the potential to prevent post-ischemic cardiac remodeling without untoward consequences in other tissues.…”
Section: Transgenic Cardiac Overexpression Studies Of Bnip3 and Nix/bsupporting
confidence: 81%
“…More importantly, they also suggest that during ischemic stress, factors other than simple upregulation are important in generating the full apoptotic response to BNIP3 in ischemic injury. Whether this is hypoxia/acidosis-mediated post-translational modification and mitochondrial translocation of BNIP3 as has been suggested (Kubasiak et al, 2002;Kubli et al, 2008), or some other as-yet unidentified factor such as nuclear translocation that is seen in ischemic brain injury (Schmidt-Kastner et al, 2004;Burton et al, 2005), is not currently known.…”
Section: Transgenic Cardiac Overexpression Studies Of Bnip3 and Nix/bmentioning
confidence: 97%
See 1 more Smart Citation
“…It is noteworthy that because HIF-1 is involved in both survival and apoptosis of tumour cells, abrogation of the apoptotic pathway caused by silencing BNIP3 may enhance HIF-1-induced survival signals within tumours. Expression of BNIP3, which is induced by hypoxic stimuli (Guo et al, 2001), has been detected in several human cancer cell lines and cardiac myocytes subjected to hypoxia (Crow, 2002;Kubasiak et al, 2002;Regula et al, 2002). In addition, Sowter et al (2003) recently reported that BNIP3 is highly expressed in the hypoxic regions of high-grade breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…44 Concerning BNIP3, a very recent report demonstrates that acidosis is necessary for this protein to induce apoptosis in hypoxic cardiac cells, likely via an effect on protein translation or stability. 45 Besides an effect on protein, acidification might also control the expression of the Bcl-2 family genes; indeed, the downregulation of antiapoptotic Mcl-1 expression, observed upon staurosporine treatment of MDCK cells, has been shown to be inhibited by a blocker of Cl À /HCO 3 À exchange. 46 This effect is interesting as expression of Mcl-1 in CHO cells has been reported to inhibit the acidification induced by staurosporine.…”
Section: Intracellular Acidification In Apoptosismentioning
confidence: 99%